Bankruptcy of Empire: Mexican Silver and the Wars Between Spain, Britain, and France, 1760–1810 - Marichal, Carlos (Cambridge University Press, 2013)
From before the time of Gibbon, historians with a global perspective have been discussing the rise and fall of empires. Today political scientists frequently speak of hegemonic states. If we review some of the best-known studies conducted over the last forty-odd years, it is possible to identify a variety of theoretical approaches adopted by those working on the history of imperial or hegemonic states. The literature is vast and includes traditional geopolitical studies with a focus on the roots of military superiority, 1 the sweeping propositions of the world-system school,2 as well as the interpretations of historical sociologists who offer explanations based on the changing capacities of states to exercise power through manipulation of capital and coercion.3 While all raise important questions, these quite general approaches do not necessarily provide convincing answers to the issue of explaining the specific reasons for the rise and/or decline of a given state or empire